Attention sports fans! The far-reaching contributions of bud sport mutants to horticulture and plant biology. Issue 1 (15th July 2018) - Foster, Toshi M; Aranzana, Maria José
Abstract: A bud sport is a lateral shoot, inflorescence or single flower/fruit with a visibly different phenotype from the rest of the plant. The new phenotype is often caused by a stable somatic mutation in a single cell that is passed on to its clonal descendants and eventually populates part or all of a meristem. In many cases, a bud sport can be vegetatively propagated, thereby preserving the novel phenotype without sexual reproduction. Bud sports provide new characteristics while retaining the desirable qualities of the parent plant, which is why many bud sports have been developed into popular cultivars. We present an overview of the history of bud sports, the causes and methods of detecting somaclonal variation, and the types of mutant phenotypes that have arisen spontaneously. We focus on examples where the molecular or cytological changes causing the phenotype have been identified. Analysis of these sports has provided valuable insight into developmental processes, gene function and regulation, and in some cases has revealed new information about layer-specific roles of some genes. Examination of the molecular changes causing a phenotype and in some cases reversion back to the original state has contributed to our understanding of the mechanisms that drive genomic evolution. Plant biology: The value of good sports: Careful analysis of unusual shoots on parent plants provides valuable insights into mechanisms driving genomic evolution. Sometimes, plants produce shoots, single flowers or fruit that are visibly and genetically different from the rest of the plant. These 'bud sports' are caused by stable mutations and usually retain the positive characteristics of the parent plant. They are useful for cultivating novel varieties, particularly in species with low genetic variability. Toshi Foster at the New Zealand Institute for Plant and Food Research in Palmerston North, New Zealand, and Maria Jose Aranzana at the Center for Research in Agricultural Genomics in Barcelona, Spain, reviewed current knowledge of bud sports and their genetic origins. Analyses of buds using next-generation sequencing is providing insights into the function and regulation of genes and mutations, with applications in agriculture and plant biology.